ARTIFICIAL INTELLIGENCE FOR TEACHING ENGLISH AS A FOREIGN LANGUAGE TO UNIVERSITY STUDENTS: ARTIFICIAL INTELLIGENCE FOR TEACHING ENGLISH AS A FOREIGN LANGUAGE TO UNIVERSITY STUDENTS - Rajapova, Guldona; Nurzhanova , Zhainash (Журнал иностранных языков и лингвистики, 2025)
Background of EFL Education English as a Foreign Language (EFL) education is vital for university students, enabling global academic and professional engagement, with over 1.5 billion learners worldwide [1]. University EFL programs focus on communicative competence in reading, writing, speaking, and listening, often using communicative language teaching (CLT) methods. Technology, from computer-assisted language learning (CALL) to mobile-assisted language learning (MALL), has reshaped EFL instruction [2]. However, large class sizes (often 1:30 student-teacher ratios) and standardized curricula limit personalization, hindering fluency development